THE BREEDING OF LOCAL VIGNA RADIATA L WITH USING MULTIGAMMA IRRADIATION TECHNIQUE (NUCLEAR) THAT TOLERANT TO DRY CONDITION, RAIN FALL, GERM, AND HIGH PRODUCTION - Pasangka, Bartholomeus; Refli, Refli (SAINSTEK, 2019)
ABSTRACT Vigna Radiata L grouped in the third important legume in Indonesia after soybean and peanut with high nutrition like as carbohydrate, protein, fat, vitamin A, B1 and C, Calcium, phosphorous, etc.The aims of the research are to develop of local Vigna Radiata L from Timor Island Indonesia with multi-gamma irradiation technique and carefully selection for obtaining variation of superior varieties. On the first research obtained five variation varieties (mutants) will be purified in the continuous research.The main method of research comprised of observation/ surveying, irradiation, purifying, carefully selection, comparative, analysis, and interpretation.The results of research on the last year (purifying step) are obtained three variations of mutant varieties with superior chemical and physical characteristics consists of: (1) time growth is quickly, (2) growth percentage is high, (3) time flowered is quickly, (4) tolerant to germ, (5) tolerant to dry condition, (6) tolerant to rain fall, (7) time harvest is lower than initial, (8) high production compared to initial. Production range of mutant varieties at four provinces on the last purifying respectively about (2.80 s/d 3.80) ton/ha (VM-1), (2.81 s/d 3.82) ton/ha (VM-2), dan (2.76 s/d 3.79) ton/ha (VM-3). The total average production of selected mutant varieties about 3.39 tons/ha. Production increase percentage of selected mutant varieties after purifying at four provinces about 47.65% (VM-1), 47.49% (VM-2), and 47.18% (VM-3) with average of production increasing percentage about 47.44%.Interval water content of selected mutant varieties and initial variety in a row about 9% up to 13% (VM-1), 9.0% up to 15% (VM-2), 9.0 up to 14% (VM-3) and 14.0% up to 23% (initial variety). The mean of water content for mutant varieties about 11.0 % (VM-1), 11.5 % (VM-2), 11.2 % (VM-3), and 17.4 % (initial variety) in dry seeds condition and ready for continuous development seeds, and (15 up to 22) % in dry seeds condition for consumption. The total mean of water content of mutant varieties for seeds to continuously development about 11.23 %. Keywords: irradiation, breeding, Vigna Radiata L, dry condition, germ